Factors Associated with Anemia Among Adolescent Girls Aged 10-19 Years in Central Kalimantan - Bellini Simangunsong; Nunik Puspitasari (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Anemia is a global adolescent health problem related to nutrition and often occurs in developing countries, including Indonesia. A lack of red blood cells or a hemoglobin level lower than 12 g/dL is known as anemia and is mainly experienced by women of childbearing age, including teenage girls. This study aims to determine the risk factors associated with anemia among adolescent girls aged 10 to 19 years in 12 Central Kalimantan schools. This study was observational-analytic with a cross-sectional design. Data (n = 355 adolescent girls) were from secondary data from the data screening for Hb levels in the School Adolescent Girls Health Education program by PT Rimba Makmur Utama. Multiple logistic regression tests analyzed the risk factors (socio-demographic and health characteristics) associated with anemia. Analysis showed that 32.1% had anemia. Most of them were 10 to 14 years old. Consumption of iron supplements in the last week (PR: 0.450, 95% CI: [0.253-0.802]) and BMI-for-age (PR: 1.599, 95% CI: [1.005-2.544]) was significantly associated with anemia. Age, parent’s education, parental income, menstruation status, consumption of iron supplements, and consumption of deworming tablets were not associated with anemia. Optimized iron supplementation programs for adolescent girls 10 to 19 ages can decrease anemia prevalence.